2018
DOI: 10.1177/1120700018760277
|View full text |Cite
|
Sign up to set email alerts
|

Early radiological and functional outcomes for a cementless press-fit design modular femoral stem revision system

Abstract: Early radiological and functional outcomes for the RECLAIM revision system showed very low levels of subsidence and good functional outcomes. There was an association with smaller diameter femoral stems and greater levels of subsidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…Hancock at al. reported in their paper no cases with subsidence over 8 mms [52]. Our average subsidence was 3.5 mms, with only one of 20 patients (5%) having more than 10 mms of stem migration.…”
Section: Discussion Of the Study With The Wagner Sl Stemcontrasting
confidence: 44%
“…Hancock at al. reported in their paper no cases with subsidence over 8 mms [52]. Our average subsidence was 3.5 mms, with only one of 20 patients (5%) having more than 10 mms of stem migration.…”
Section: Discussion Of the Study With The Wagner Sl Stemcontrasting
confidence: 44%
“…Several studies do report outcomes of using several different stems within the same cohort, making it difficult to draw conclusions about any singe stem (Katakam et al 2021;Parry et al 2018;Wood et al 2019). Hancock et al retrospectively reviewed 48 revision THAs using the same femoral stem as our study with mean 1 year follow-up (Hancock et al 2018). Compared to our study, Hancock et al found a higher incidence of postoperative periprosthetic infections (7.41% vs 10.42%), dislocations (0.0% vs 4.2%), revision for subsidence (0.0% vs 2.08%), and lower mean subsidence (2.07mm vs 1.1mm) (Hancock et al 2018).…”
Section: Radiographic Analysismentioning
confidence: 99%
“…Hancock et al retrospectively reviewed 48 revision THAs using the same femoral stem as our study with mean 1 year follow-up (Hancock et al 2018). Compared to our study, Hancock et al found a higher incidence of postoperative periprosthetic infections (7.41% vs 10.42%), dislocations (0.0% vs 4.2%), revision for subsidence (0.0% vs 2.08%), and lower mean subsidence (2.07mm vs 1.1mm) (Hancock et al 2018). Pawar et al found a lower rate of reoperation for recurrent infection (3.51% vs 7.41%), but a higher rate of dislocation (5.26% vs 0.0%, Table 2) and higher subsidence (4.5 mm vs 2.07mm) (Pawar et al 2022).…”
Section: Radiographic Analysismentioning
confidence: 99%
“…The majority of re‐revisions are caused by aseptic loosening—potentially introduced by excessive micromotion between stem and bone 14–17 . In particular, stem subsidence occurs frequently with cementless revision stems 18,19 . Postoperative stem subsidence less than 2 mm 20 and micromotions of less than 30 µm are considered harmless, 21,22 while micromotions >150 µm are considered an unfavorable condition for osseointegration 23 …”
Section: Introductionmentioning
confidence: 99%
“…with cementless revision stems. 18,19 Postoperative stem subsidence less than 2 mm 20 and micromotions of less than 30 µm are considered harmless, 21,22 while micromotions >150 µm are considered an unfavorable condition for osseointegration. 23 Patient-related factors such as femur shape or bone quality but also upper femoral curvature (UFC) may have an impact on the primary stability of cementless revision stems.…”
mentioning
confidence: 99%